2021
DOI: 10.1097/qai.0000000000002788
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of Self-reported Discrimination in HIV Health Care Settings Among Persons With Diagnosed HIV in the United States, Medical Monitoring Project, 2018–2019

Abstract: Background: HIV-related discrimination in health care settings is associated with negative health outcomes among persons with HIV (PWH). This article describes and compares differences in the prevalence of self-reported experiences with discrimination in health care settings by sociodemographic and clinical care factors among persons with diagnosed HIV in the United States. Methods:We analyzed interview and medical record data collected during June 2018-May 2019 from 3850 PWH who had received HIV care in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The area has a low level of economic development and insufficient human resources for health compared to other areas. The GDP per capita in the area is lower than the average in Luzhou, and the low level of economic development may be one of the reasons for the high prevalence of AIDS in the township [ 28 , 29 ]; the cold spots in Luzhou from 2011 to 2020 were mainly concentrated in Xuyong county and southern Gulin county. The results of the small-scale hotspot analysis also verified the influence of urbanization, population density, and GDP per capita on the spatial and temporal distribution of HIV and AIDS in Luzhou.…”
Section: Discussionmentioning
confidence: 99%
“…The area has a low level of economic development and insufficient human resources for health compared to other areas. The GDP per capita in the area is lower than the average in Luzhou, and the low level of economic development may be one of the reasons for the high prevalence of AIDS in the township [ 28 , 29 ]; the cold spots in Luzhou from 2011 to 2020 were mainly concentrated in Xuyong county and southern Gulin county. The results of the small-scale hotspot analysis also verified the influence of urbanization, population density, and GDP per capita on the spatial and temporal distribution of HIV and AIDS in Luzhou.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to experiences reported by all U.S. persons with HIV, the most prevalent HIV stigma domain among Hispanic persons with HIV was concern about disclosure of HIV status ( 2 ), and the most reported form of health care discrimination was feeling that a clinician was not listening to them ( 3 ). This underscores the importance of addressing disclosure concerns when designing interventions to reduce HIV stigma.…”
Section: Discussionmentioning
confidence: 87%
“…A previous report found that the percentages of Hispanic persons who received HIV care, were retained in care, and were virally suppressed were lower than those among non-Hispanic White persons with HIV ( 1 ). HIV stigma and discrimination are human rights issues associated with adverse HIV outcomes; eliminating stigma and discrimination among persons with HIV is a national priority * , † , § ( 2 , 3 ). CDC analyzed data from the Medical Monitoring Project (MMP), an annual, cross-sectional study designed to report nationally representative estimates of experiences and outcomes among adults with diagnosed HIV.…”
mentioning
confidence: 99%
“…For example, providers could write 90-day instead of 30-day prescriptions to improve adherence [16] if patients have difficulties (e.g., lack of transportation access) [17] obtaining monthly prescriptions. Healthcare clinics may also implement antistigma and antidiscrimination interventions [18] given that MSM, racial/ethnic minorities, and persons living in poverty tend to report greater experiences of stigma and discrimination [18][19][20][21], Copyright © 2024 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%